The effects of combining aerobic and hypertrophy oriented resistance training on body composition, muscle hypertrophy and exercise satisfaction in physically active adults - Ling, Jerrican Tan Aik (2023)
This study investigated the effects of combined aerobic and heavy resistance training on body composition, muscle hypertrophy, and exercise satisfaction in physically active adults in comparison to heavy resistance (hypertrophy-aimed) training alone. A total of 22 healthy, physically active male adults between the ages of 18 and 35 who did not practise muscle hypertrophy training before completed the programme. They were randomly assigned to two groups: the resistance training group and the combined group (resistance training and aerobic training). Resistance training consisted of a three-day muscle group split (2–3 exercises per muscle group, 8 sets per muscle group, 6–12 RM), while aerobic training consisted of a three-times-per-week aerobic interval training programme. Both groups were exposed to 8 weeks of training interventions, one group to resistance training alone and another to a combined training of resistance training plus aerobic training, at the end of which variables of body composition, muscle hypertrophy, and exercise satisfaction were statistically analysed using SPSS 27.0 software. For body composition variables, combined training shows reduction in bodyweight, body fat, fat mass and increment in lean body mass within the group. For muscle hypertrophy variables, chest girth has improved within each the resistance training only and combine training. Shoulder girth and hips girth improved significantly within the resistance training only group with no improvements in the combined group. The combined training group improved in the thighs girth with no improvement of this variable observed in the resistance training group. Overall, it is impossible to state unequivocally that one training modality was superior to another in the body composition and muscle hypertrophy cluster. Exercise satisfaction has improved from the pre-test to the post-test within the groups. From pre- to post-testing, both intervention groups improved exercise satisfaction (both at p < 0.05). There was, however, no difference between the groups (resistance training versus combined training before the intervention and after the training; (p > 0.05). In conclusion, aerobic training can be added to muscle hypertrophy routines without the risk of decreasing the effects of muscle hypertrophy. Increased exercise satisfaction signalizes that although deemed monotonous, aerobic workouts when added to hypertrophy routines, exercise satisfaction improves significantly.